Marcadores de estresse oxidativo e concentrações de primaquina e carboxiprimaquina em pacientes com malária por Plasmodium vivax - RODRIGUES, Luiz Carlos de Souza (Universidade Federal do Pará, 2017)
The changes in redox cycle has been associated with the physiopathology of severity of malaria in experimental models and in humans. However, a few studies evaluated the changes in redox equilibrium of patients with no severe malaria by P.vivax, which comprise the majority of the cases of disease. The variations of oxidative damage and the respective antioxidant response of human host were not compared before, during and after chemotherapy. Also, the mechanisms responsible by the generation of free radical in each phase that is, the heme degradation, respiratory burst of macrophages or antimalarials uses, were not determined. The objective of this study was to estimate the levels of biomarkers of oxidative damage and the respective antioxidant response, as well as primaquine and carboxyprimaquine whole blood levels in malaria by P. vivax. Therefore, were enrolled 38 patients with slide confirmed infection by P. vivax followed by 28 days. Serial blood samples were collected on pre-doses samples (D0) and on D2, D7 and D14. The oxidative damage and the antioxidant defense were estimated by the spectrophotometric measures of thiobarbituric acid reatives substances and methemoglobinemia, and by total antioxidant capacity and reduced glutathione, respectively. The control group consisted of 19 healthy volunteers matched for age and gender ratio. Primaquine and its major metabolite were determined by high performance liquid chromatography. The results revealed that the disease occurred in male patients of working age. Haematological parameters remained constant during the study. Biochemical evaluation showed a significant decrease in HDL-cholesterol levels during the study. Methemoglobinemia was associated with antimalarials uses, because the levels were similar to control group and increased significantly during the treatment. The levels of thiobarbituric acid reatives substances were associated with plasmodium and probably respiratory burst of macrophages, because they were higher than control group on D0, and no significant changes were observed after antimalarials usage. Total antioxidant capacity and oxidative stress levels were similar during the study as well as in the control group. The levels of reduced glutathione decreased significantly during the study and doesn’t be associated with both parasitaemia. Primaquine does not show a significant accumulation, and the concentrations of parent drug and its carboxyl metabolite were not associated with methemoglobinemia and thiobarbituric acid reatives substances levels.